P826 High prevalence of cervical HR-HPV in immigrant women originating from sub-saharan africa and living in orléans, france. (14th July 2019) - Sydney Mboumba Bouassa, Ralph; Gubavu, Camelia; Matta, Mathieu; Robin, Leman; Veyer, David; Gravier, Anne; Hocqueloux, Laurent; Prazuck, Thierry; Péré, Hélène; Bélec, Laurent
Abstract : Background: We herein assess the HPV detection and HPV-related cervical lesions in immigrant African women living in France. Methods: In 2018, immigrant African adult women attending for sexual health and HIV care a French healthcare facility, were included and subjected to endocervical swabs and Pap smear. HPV DNA was detected by multiplex real-time PCR (AnyplexTM II HPV28, Seegene, Seoul, South Korea). Results: 50 African immigrant women (mean age, 41.7) residing in France for an average of 10.7 years (range 1–32), including 74.0% of HIV-positive and 26.0% of HIV-negative, were prospectively included. HPV prevalence was 68.0%, with 56.0% of HR-HPV and 24.0% of multiple HPV. Unexpectedly, the non-vaccine HR-HPV-68 (20.0%) was the predominant genotype, followed by the Gardasil-9 ® vaccine HR-HPV-58 (14.0%). HPV-16 and HPV-18 were respectively detected in 6.0% and 10.0%. HIV-infected women were more infected with HR-HPV (62.2%) and multiple HR-HPV (16.2%) than HIV-negative women (38.4% and 7.7%, respectively), (P=0.19 and P=0.66, respectively). Most women (84.0%) showed normal cytology, but 16.0% exhibited cervical abnormalities, including 6.0% of Low-grade Squamous Intraepithelial Lesions (LSIL) and Abnormal Squamous Cells with Unknown Significance (ASCUS), and 4.0% of High-grade Squamous Intraepithelial Lesions (HSIL). HPV-16 and HPV-18 were detected in one woman with HSIL. Finally, 87.5% of the study women with cervical abnormalities were HIV-positive, while only one HIV-negative woman showing cervical abnormalities. Conclusion: These findings highlight the unsuspected high burden of cervical HR-HPV infections often associated with cervical abnormalities in the first-generation immigrant women originating from sub-Saharan Africa and residing in France. These observations also point out the atypical epidemiological profile of cervical HPV infection with a rare and non-vaccine high-risk genotype being the most detected HPV, raising thus a concern about the low predictive efficacy of the Gardasil-9 ® vaccine in the prevention of the main genotypes circulating in these specific population residing in France. Disclosure: No significant relationships.